Life Domains and Lifestyle of Older Adults Living in a Nursing Home: A Pilot Study. - Uceda-Portillo, Cristian; Calvo-Arenillas, José-Ignacio; Moruno-Miralles, Pedro (Inquiry (00469580), 2023)
Although the preventive occupational therapy intervention program Lifestyle Redesign® has proven to be effective in maintaining and improving the health and quality of life of older adults, a similar program has not yet been culturally adapted to the Spanish population. As a preliminary step in developing a lifestyle intervention tailored to healthy Spanish older adults living in a nursing home (Lifestyle Choice; originally in Spanish "Elección de Estilo de Vida"), we aimed to identify and describe the life domains of this population and determine overlap with content areas addressed in the Lifestyle Redesign® program. An observational cross-sectional study was carried out using quantitative methods, including 30 healthy older adult residents in the "Virgen del Prado" nursing home in Talavera de la Reina (Toledo), based on the development of a questionnaire and a survey. Six life domains were identified: self-care, sleep and rest, mobility, personal safety, health maintenance, spirituality, and free time usage. The results of this study reveal important overlaps with content areas of Lifestyle Redesign®, suggesting that it may be feasible to develop a lifestyle intervention ("Elección de Estilo de Vida") tailored to the sociocultural features of the healthy Spanish population over 65 years old living in nursing homes.